Temperature performance of stainless steel AISI420B orthopedic drill bits simulation study - Mohd, Afza Nizam; Abu Husain, Mohd Khairi; Sarip, Shamsul; Ismail, Roslan (Penerbit Akademia Baru, 2022)
In orthopedic and trauma surgery, the drilling of bone is the process of preparing, making, and enlarging a hole of circular crosswire in a solid anisotropic material bone structure. The failure of irreversible osteonecrosis occurs when the temperature rises to 47 °C or higher during bone drilling. Osteonecrosis is a disorder that leads to the death of bone tissue cells, resulting in weaker contact between implants and bone, and in some cases, the loss of strong and stable attachment to the bone. Previous studies had concentrated on drill bit material, design, point angle, force, speed, and feed rate. This study outlines the technique for developing a drilling-related finite element model to verify the drilling process’s efficacy using a computer simulation approach. Software LS-DYNA © 2011-2020 LST was used to conduct a drilling model based on the finite element (FE) technique. The temperature behavior of orthopedic chromium type martensitic magnetic stainless steel AISI420B twist drill bit (Ø 4.3 mm) was determined. The findings were quantified, and the outcomes of the simulated and actual evaluations were compared. The surgeon’s typical drilling technique or pattern was used in this study, with a penetration angle of no more than 30°, and performed using a battery-powered surgical hand drill. A forward-looking infrared (FLIR) camera for temperature detection was used to record drill bits thermal data throughout the experiment. The utilization of two factorial analyses in the design of experiment (DOE) and analysis of variance (ANOVA) revealed that the simulation result had higher mean performance confirmation than the actual experimental result, with a difference of 10.9102%. The AISI420B showed good heat conductivity, and minor wear than typical stainless steel drill bits in the market for bone drilling. Therefore, the AISI420B stainless steel twist drill bit tested able to perform well for bone drilling.